Analysing the Effect of Monsoon on the Indian Stock Market - Shukla, Trilok Nath (Indian Journal of Research in Capital Markets, 2016)
Everyone emphasizes the impact of monsoon on the Indian economy and given our high dependence on monsoon rains, the agricultural sector is the most vulnerable to the changing rain patterns. But what is the actual impact of the monsoons on the stock markets? You will be surprised to know the negative correlation between the two. As per an article in Business Standard, in the last one decade, there is hardly enough correlation to suggest that monsoon can have much bearing on the market sentiments. In fact, as per the data, the BSE-Sensex returns were the highest in the year when rainfall was most deficient with regards to long period average (LPA).However, it is part psychological and part actual. Monsoon seems to be the only respite that Indian companies can look forward to this year (2016), after two continuous bad monsoon years. Falling rupee, high fiscal deficit, flight of foreign funds and poor earnings, these have been the only themes in the India story for many quarters now. However, a good monsoon might bring good tidings, at least for some companies. Good monsoon improves the rural demand for products, increasing the purchasing power and companies such as HUL, Dabur, Godrej Consumer, and ITC benefit a lot. Demand of two wheelers, low cost cars, and tractors also increase during a good monsoon, which is helpful for M&M, Escorts, Eicher, Maruti, and Bajaj Auto. High farm production also lowers raw material costs for companies that make packaged foods, for instance, Britannia, GSK Consumer, ITC, and Nestle. Data shows a close link between rains and fortunes of FMCG companies. Fertilizer and irrigation companies such as Chambal, RCF, Jain Irrigation, etc. get a direct boost due to better rainfall. Once the rains support better agricultural output, the windfall gains are witnessed automatically in the manufacturing and services sector as well. Hence : Better Monsoon--> Better Crops --> Better Agriculture --> Increase in disposable income --> Better sales for manufacturing and services companies --> Higher Profitability -->Higher Dividends/Higher stock prices --> Better economic performance.